Neuroanatomical correlates of emotion-processing in children with unilateral brain lesion: A preliminary study of limbic system organization. (2nd November 2018) - Ng, Rowena; Lai, Philip; Brown, Timothy T; Järvinen, Anna; Halgren, Eric; Bellugi, Ursula; Trauner, Doris
ABSTRACT: In this study, MRI and DTI were employed to examine subcortical volume and microstructural properties (FA, MD) of the limbic network, and their relationships with affect discrimination in 13 FL (6 right FL, M  = 10.17 years; 7 left FL; M =  10.09) and 13 typically-developing children (TD; M =  10.16). Subcortical volume of the amygdala, hippocampus and thalamus and FA and MD of the fornix and anterior thalamic radiation (ATR) were examined. Results revealed no group differences across emotion-perception tasks or amygdalar volume. However, contrasting neuroanatomical patterns were observed in right versus left FL youth. Right FL participants showed increased left hippocampal and thalamic volume relative to left FL participants; whereas, the latter group showed increased right thalamic volume. DTI findings also indicated right FL children show greater MD of right fornix than other groups, whereas, left FL youth showed greater MD of left fornix. Right FL youth also showed lower FA of right fornix than left FL children, whereby the latter showed greater FA of left fornix and ATR. Differential associations between DTI indices and auditory/visual emotion-perception were observed across FL groups. Findings indicate diverging brain-behavioral relationships for emotion-perception among right and left FL children.